Isogeometric boundary element method for isotropic damage elastic mechanical problems. (April 2023) - Li, Kunpeng; Yang, Ting; Jiang, Wei; Zhao, Kaiqiang; Zhao, Kaibing; Xu, Xinyang
Abstract: In this work, a complex isotropic damage mechanics structural model is developed using the isogeometric method to study the strain displacement and influence factors in isotropically damaged elastics. The proposed modeling method can be constructed dynamically by introducing control points and weight coefficients, which improves the accuracy and eliminates mesh errors, and the boundary element method is used for theoretical analysis and calculation of damage mechanics. For the description of irregular geometric models, the isogeometric method has unparalleled superiority. The isogeometric method can seamlessly connect the geometry generated by the advantages of CAD and CAE, and the combination of the two methods is very useful for the future extension of IGABEM to practical engineering applications. At the same time, we use the source point isolation method to establish the boundary-domain integral equations and use the radial integration method to solve the domain integrals. Compared with the traditional boundary element method, the isogeometric boundary element method makes the construction of complex models simple. The numerical results show that the numerical method has good stability and robustness, which provides strong support for further software integration. Highlights: A novel numerical algorithm is used for damage mechanics, which is utilized as a reference solution for solving true engineering issues. By using spline curve for modeling, the application of boundary element method is greatly increased. The isogeometric boundary element method is used to solve the damage fracture mechanics problem for the first time.